Faith-Based Organizations’ Humanitarian Work from the Disaster Risk Governance Perspective: Lessons from Covid-19 Pandemic in Indonesia - Prianto, Andi Luhur; Usman, Sunyoto; Amri, Aqmal Reza; Nurmandi, Achmad; Qodir, Zuly; Jubba, Hasse; Ilik, Goran (Fakultas Syariah UINSI Samarinda, 2023)
The Covid-19 pandemic has represented a risk to human life. “What is the role of religion in disaster risk governance” is a critical question for Faith-Based Organizations (FBOs) in times of crisis. As a religious observance form, FBOs must correlate sacred religious doctrines with practical problems of human life and build sustainable actions in disaster governance. This study seeks to examine further the significance of religion-based organizations in the agenda for handling the adverse effects of the Covid-19 pandemic. This paper uses qualitative research methods with NVivo 12 Plus as a data processing tool. The results of this study indicate that in emergency response, recovery, prevention, and preparedness, FBOs in Indonesia are integrated and encourage interfaith collaboration in handling the COVID-19 pandemic. The FBOs demonstrate the ability to collaborate across non-state sectors and play a multidimensional role. Through the sacred doctrine of religion, FBO mobilizes its members to comply with government policies and participate in efforts to mitigate the adverse effects of the covid 19 pandemic. Thus, maslahah, also known as the objectives of sharia, is an essential Islamic law principle that encourages Islamic organizations to engage in disaster risk governance efforts during the Covid 19 pandemic.